Integrated Insights into Metabolic and Bariatric Surgery: Improving Life Quality and Reducing Mortality in Obesity - Ruxandra-Cristina Marin; Andrei-Flavius Radu; Paul Andrei Negru; Ada Radu; Denisa Negru; Raluca Anca Corb Aron; Teodora Maria Bodog; Ruxandra Florina Bodog; Paula Bianca Maghiar; Roxana Brata (Medicina)
Metabolic and bariatric surgery (MBS) is an effective intervention for patients with severe obesity and metabolic comorbidities, particularly when non-surgical weight loss methods prove insufficient. MBS has shown significant potential for improving quality of life and metabolic health outcomes in individuals with obesity, yet it carries inherent risks. Although these procedures offer a multifaceted approach to obesity treatment and its clinical advantages are well-documented, the limited understanding of its long-term outcomes and the role of multidisciplinary care pose challenges. With an emphasis on quality-of-life enhancements and the handling of postoperative difficulties, the present narrative review seeks to compile the most recent findings on MBS while emphasizing the value of an integrated approach to maximize patient outcomes. Effective MBS and patients’ management require a collaborative team approach, involving surgeons, dietitians, psychologists, pharmacists, and other healthcare providers to address not only physiological but also psychosocial patient needs. Comparative studies demonstrate the efficacy of various MBS methods, including Roux-en-Y gastric bypass and laparoscopic sleeve gastrectomy that may considerably decrease morbidity and mortality in individuals with obesity. Future studies should target long-term patient treatment, and decision making should be aided by knowledge of obesity, comorbidity recurrence rates, and permanence of benefits.